Identifikasi Penambahan Air pada Daging Sapi dengan Metode Filter Paper Press dan Konduktivitas Listrik - Nararya Adinata; Denny Widaya Lukman; Etih Sudarnika (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Beef meat has a complete nutritional content, the high prices in the market causing some unscrupulous traders to cheat by adding water to meat to get more weight. This beef meat has a bad quality, so needs the right method to identify the quality of beef meat in the field. This study was designed to identify the addition of water to beef meat by measuring the water holding capacity (filter paper press method) and electrical conductivity (EC meter). The experimental used one hundred bovine longisimus dorsi and the samples were divided into five groups. One group as a control and four other groups were treatment group. The treatment groups were injected by water with a volume of 1%, 2%, 3%, and 4% of the sample weight and all groups were repeated for twenty times. The results were analyzed by ANOVA and Duncan Multiple Range test. The data showed that the addition of water by injection in beef meat of treatment group 2%, 3%, and 4% had a significant influence on water holding capacity and electrical conductivity (p<0.05). Pearson correlation results showed a strong to very strong correlation with value in control group (r=0.704; p<0.01), treatment group 1% (r=0.628; p<0.01), 2% (r=0.700; p<0.01), 3% (r=0.642; p<0.01) and 4% (r=0.760; p<0.01). Based on the result of the study, it is known that a water increase in beef at least 2% of the weight significantly affected water holding capacity and it can be identified by using electrical conductivity meter.